New Approaches for Gummy Smile Treatment: A Review - H Sharif; Sh Aghayan (Islamic Azad University, 2023)
Background and Aim: Nowadays, facial esthetics has become the main concern for many people. Gummy smile (GS) is a common complaint that affects the esthetics and psychological status of patients. The aim of this study was to review GS treatment options.   Materials and Methods: An electronic search was conducted in three databases of PubMed, Wiley and Cochrane Library from January 2015 up to August 2021. According to the eligibility criteria, a total of 41 relevant papers were retrieved and reviewed. Results: Based on the available data, several techniques have been reported for GS treatment, such as lip repositioning, crown lengthening, orthognathic surgery, laser application, botulinum toxin (BT) injection, hyaluronic acid injection, and micro autologous fat transplantation (MAFT). Combination of two or three of these techniques may yield a better result. Conclusion: A wide variety of procedures are available based on the cause of GS. The new, less invasive, faster and safer alternative techniques were shown to be feasible with a long-lasting result and minimal postoperative sequelae. Such treatment options for various types of GS can lead to significant improvement in smile esthetics with high patient satisfaction.